Regulation of Tocopherol Biosynthesis During Fruit Maturation of Different Citrus Species - Rey, Florencia; Zacarias, Lorenzo; Rodrigo, María Jesús (Frontiers in Plant Science, 2021)
Tocopherols are plant-derived isoprenoids with vitamin E activity, which are involved in diverse physiological processes in plants. Although their biosynthesis has been extensively investigated in model plants, their synthesis in important fruit crops as Citrus has scarcely been studied. Therefore, the aim of this work was to initiate a physiological and molecular characterization of tocopherol synthesis and accumulation in Citrus fruits during maturation. For that purpose, we selected fruit of the four main commercial species: grapefruit (Citrus paradisi), lemon (Citrus limon), sweet orange (Citrus sinensis) and mandarin (Citrus clementina), and analyzed tocopherol content and the expression profile of 14 genes involved in tocopherol synthesis during fruit maturation in both the flavedo and pulp. The selected genes covered the pathways supplying the tocopherol precursors HGA (TAT1 and HPPD) and PPP (VTE5, VTE6, DXS1 and 2, GGPPS1 and 6, and GGDR) and the tocopherol-core pathway (VTE2, VTE3a, VTE3b, VTE1 and VTE4). Tocopherols accumulated mainly as α- and γ-tocopherol, and α-tocopherol was the predominant form in both tissues. Moreover, differences were detected between tissues, among maturation stages and genotypes. Contents were higher in the flavedo than in the pulp during maturation, and while they increased in the flavedo they decreased or were maintained in the pulp. Among genotypes, mature fruit of lemon accumulated the highest tocopherol content in both the flavedo and the pulp, whereas mandarin fruit accumulated the lowest concentrations, and grapefruit and orange had intermediate levels. Higher concentrations in the flavedo were associated with a higher expression of all the genes evaluated, and different genes are suitable candidates to explain the temporal changes in each tissue: i) in the flavedo, the increase in tocopherols was concomitant with the up-regulation of TAT1 and VTE4, involved in the supply of HGA and the shift of γ- into α-tocopherol, respectively; ii) in the pulp, changes paralleled the expression of VTE6, DXS2 and GGDR, which regulate PPP availability. Also, certain genes (i.e. VTE6, DXS2 and GGDR) were co-regulated and shared a similar pattern during maturation in both tissues, suggesting they are developmentally modulated.